“LET’S WRITE A CAPTION!”: UTILIZING INSTAGRAM TO ENHANCE ESP STUDENTS’ WRITING SKILLS - Arif Nugroho; Any Rahmawati (BASIS (Bahasa dan Sastra Inggris), 2020)
The integration of technology in language classroom is a prerequisite in the twenty-first century teaching. Social media as part of technology advancement has a great potential to improve students’ motivation and the efficacy of learning a language. Therefore, the present study sheds light on the effect of the use of Instagram on ESP students’ writing ability. It involved 36 Indonesian ESP students majoring in Sharia Banking of a university in Surakarta Indonesia. The pre-experimental research was conducted in eight meetings, including the writing pre-test and post-test. The students were assigned to write a descriptive essay by means of Instagram as the instructional medium. A questionnaire was also given to reveal their perceptions toward the use of Instagram to practice writing. The result of the data analysis showed that there was a significant difference on the students’ writing scores between the pre-test and the post test. The finding of this study is expected to provide significant contribution to the realm of English for specific purposes (ESP) teaching in Indonesia. Based on the findings, some insights are given for teachers and future researchers about the potential use of Instagram on the teaching of writing.